From New Haven to Nineveh and beyond three centuries of Near Eastern learning at Yale - Foster, Benjamin R. 1945- (Lockwood Press, 2023)
"Over the course of three centuries, Yale has been actively and seriously engaged in Near Eastern learning, in both senses of the term-training students in the knowledge and skills needed to understand the languages and civilizations of the region, and supporting generations of scholars renowned for their erudition and pathbreaking research. From New Haven to Nineveh and Beyond traces the history of these endeavors through extensive use of unpublished archival materials, including letters, diaries, and records of institutional decisions. Developments at Yale are set against the wider background of changing American attitudes towards the Near East, as well as evolving ideas about the role of the academy and its curriculum in educating undergraduate and graduate students. Numerous illustrations, many of them previously unpublished, round out this vivid portrait of three centuries of Near Eastern learning at Yale"--
2309
Keywords: Yale University / Department of Near Eastern Languages and Civilizations; Public opinion / United States; Middle East / Study and teaching (Higher) / United States / History; Middle East / Foreign public opinion, American; Opinion publique / États-Unis; Education, Higher; Public opinion; Public opinion, American; Middle East; United States; History